2021
DOI: 10.52095/gp.2021.1392.1015
|View full text |Cite
|
Sign up to set email alerts
|

Association of perceived isolation and resilience with self-rated mental health among undergraduate medical students in Nepal during the COVID-19 pandemic

Abstract: Background:The COVID-19 pandemic has devastatingly affected the entire world and destroyed the equilibrium of every sphere of life. Like other groups of people, medical students of Nepal have been facing the conditions of lockdown and social isolation that have arisen because of the pandemic. Objective: We aimed to see the relationship of perceived isolation and resilience with self-rated mental health among undergraduate medical students in Nepal. Materials and methods:A web-based online survey was carried ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 30 publications
2
3
0
Order By: Relevance
“…Membership in organizations and groups was also found to increase mental health. Other findings of the present study indicated that a history of physical illness decreases mental health, which is consistent with other studies [19,22,30,31]. The reason for this finding is that at an old age, a person's ability to adhere to principles and maintain their health is considerably diminished following chronic illnesses and disabilities, thereby reducing one's mental health.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Membership in organizations and groups was also found to increase mental health. Other findings of the present study indicated that a history of physical illness decreases mental health, which is consistent with other studies [19,22,30,31]. The reason for this finding is that at an old age, a person's ability to adhere to principles and maintain their health is considerably diminished following chronic illnesses and disabilities, thereby reducing one's mental health.…”
Section: Discussionsupporting
confidence: 92%
“…The results of this study showed that mental health differs at varying age levels; i.e., mental health degenerates with age, which is confirmed by other studies [20][21][22][23][24]. Given their disabilities and physical problems, as the elderly get older, they tend to gradually distance themselves from society and have less engagement in activities.…”
Section: Discussionsupporting
confidence: 82%
“…In addition, when comparing rates of mental problems among people living in provinces with and without COVID-19 cases, we observed that rates of depression and anxiety were relatively higher among participants living in provinces with COVID-19 outbreaks than those not living in provinces with pandemic (depression: 35.2% vs. 27%; anxiety: 38.6% vs. 32.4%, respectively). This insignificant difference in data could be attributed to the fact that COVID-19 did not only affect people living in endemic areas but also influenced people living in non-endemic areas with feelings of uncertainty and fear of infections [7,10].…”
Section: Discussionmentioning
confidence: 99%
“…The score of each domain was computed by summing scores of items within each domain and then multiplying by 2, resulting in a total score from 0 to 42 in each domain. Each domain of DASS-21 was divided into five levels [27]: Depression: normal (0-9), mild (10)(11)(12)(13), moderate (14)(15)(16)(17)(18)(19)(20), severe (21)(22)(23)(24)(25)(26)(27) and extremely severe (� 28), Anxiety: normal (0-7), mild (8)(9), moderate (10)(11)(12)(13)(14), severe (15)(16)(17)(18)(19), and extremely severe (� 20), and Stress: normal (0-14), mild (15)(16)(17)(18), moderate (19)(20)(21)(22)(23)(24)(25), severe (26-33) and extremely severe (� 34)…”
Section: Depression Anxiety and Stress Scale-21 Items (Dass-21)mentioning
confidence: 99%
See 1 more Smart Citation